2019
DOI: 10.1111/mbe.12217
|View full text |Cite
|
Sign up to set email alerts
|

Preschoolers' Associations Between Space and Numbers Can Be Biased by Surface Area

Abstract: People associate numbers and horizontal space. This association has been demonstrated by the so‐called SNARC (Spatial‐Numerical Association of Response Codes)‐effect, with Western participants responding faster to larger numbers with their right hand and vice versa for smaller numbers. SNARC‐like effects have also been reported for preschoolers. However, it remains unclear whether children's SNARC‐effects are exclusively based on number or whether nonnumerical factors such as surface area can also play a role.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…This was true although all of the children in our sample were regularly exposed to joined book reading activities at their homes, and although half of the children had some very rudimentary experience with writing. While previous research has shown that such activities sometimes suffice to introduce spatial biases in preschool children-especially with regard to the so-called 'mental number line' in which smaller numbers are associated with the left and larger numbers with the right side of space [65][66][67][68], others find that directional biases are not yet present at a preschool age [32,43]. In line with these latter findings, our results suggest that some basic exposure to reading is not sufficient but rather that more substantial experience with reading and writing is necessary for introducing spatial biases during picture naming.…”
Section: Plos Onementioning
confidence: 99%
“…This was true although all of the children in our sample were regularly exposed to joined book reading activities at their homes, and although half of the children had some very rudimentary experience with writing. While previous research has shown that such activities sometimes suffice to introduce spatial biases in preschool children-especially with regard to the so-called 'mental number line' in which smaller numbers are associated with the left and larger numbers with the right side of space [65][66][67][68], others find that directional biases are not yet present at a preschool age [32,43]. In line with these latter findings, our results suggest that some basic exposure to reading is not sufficient but rather that more substantial experience with reading and writing is necessary for introducing spatial biases during picture naming.…”
Section: Plos Onementioning
confidence: 99%